2015
DOI: 10.17261/pressacademia.2015312989
|View full text |Cite
|
Sign up to set email alerts
|

The impact of strategic innovation management practices on firm innovation performance

Abstract: In a highly competitive environment, innovation is the essential key to a firm obtaining a dominant position and gaining higher profits. Therefore, the understanding of which strategic innovation management practices lead to success is very important. The purpose of the study is to investigate the impact of innovation strategy, organizational structure, innovation culture, technological capability and customer and supplier relationships, which appear in the literature as strategic innovation management practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 69 publications
(115 reference statements)
4
44
0
6
Order By: Relevance
“…There is a support for Hypothesis 2 with 10% of significance. This result is consistent with findings of Kalay and Lynn (2015) determining the positive impact of strategy for innovation on innovation success in a company. It is really important for a company to plan innovative strategy as well as establish policy for innovation such as encouraging innovative ideas and diffusing them in the company.…”
Section: Hypothesissupporting
confidence: 92%
“…There is a support for Hypothesis 2 with 10% of significance. This result is consistent with findings of Kalay and Lynn (2015) determining the positive impact of strategy for innovation on innovation success in a company. It is really important for a company to plan innovative strategy as well as establish policy for innovation such as encouraging innovative ideas and diffusing them in the company.…”
Section: Hypothesissupporting
confidence: 92%
“…Radical innovations bring about extreme modifications in an organization's activity and demonstrate an obvious move from what was done before, whereas incremental innovation brings about a more moderate level of change from initial practices. Radical type innovation has a greater chance of occurrence when an organization has an informal, centralized structure; while those of the incremental kind are likely to happen in organizations that have structures which are decentralized and complex (Kalay and Lynn, 2015).…”
Section: Structural Theories Of Innovationmentioning
confidence: 99%
“…According to some scholars, an organizational structure based on formal control may increase innovative performance by enabling coordination among different functional units, increasing the level of cost effectiveness, decreasing uncertainty and minimizing mistakes (Schultz et al, 2013). On the other hand, various authors (Hage and Aiken, 1967;West, 2000;Kalay and Lynn, 2015) have shown that a negative relationship exists between formalization and innovation. Increasing formalization reduces the extent of freedom of employees by prescribing procedures and potentially sanctioning some courses of action, providing specific directions as to appropriate actions, directing and enforcing these actions, and constraining employees' ability to engage in discretionary behaviors (Raub, 2007).…”
Section: The Impact Of Formalization On Management Innovationmentioning
confidence: 99%
See 2 more Smart Citations